Gestão da Informação e do Conhecimento em Cooperativa de Crédito: uso de tecnologias existentes no controle do fluxo informacional cooperativo - Santos, Kayo Thalys Medeiros dos (2023)
We live in a generation in which information transcends different paradigms, formats and media, focusing on access to information. In the business world, it facilitates the process of information retrieval and information and knowledge management. The research question was to find out how existing technologies can contribute to Information and Knowledge Management in the control of information flows in an innovative way, using the Sicredi Credit Cooperative in Aracaju, SE, as a case study. The aim was to observe the organization's information flow, with a view to dissemination, preservation and control, in order to facilitate access and modernization of the Cooperative's documentary fund, taking into account aspects of digital accessibility to documents. The specific objectives were: to highlight the activities related to Information Management (IM) and Knowledge Management (KM) in terms of strategies related to the use of existing technologies to control the flow of information and innovation; to draw up a manual as an information and knowledge tool for the organization's employees, so as to make it possible to optimize the cooperative's administrative processes and document management. From a methodological point of view, this research is bibliographical, qualitative, descriptive, exploratory, documentary and a case study. The end product was the construction of an Information and Knowledge Management Manual for credit unions, with the aim of highlighting the use of technology in an innovative way and explaining the importance of information professionals in the search for the best results. It is understood that there are difficulties in managing and controlling the flow of information in administrative activities, given the lack of and demand for professionals with specific qualifications in the area of Information Science. The product of this study will be in the possession of the cooperative organization Sicredi Aracaju, serving as an instrument that generates knowledge and stimulates innovation and new knowledge for current and future employees, and as a reference guide for information management in the institution.